Impact of Carbon Support Meso‐Porosity on Mass Transport and Performance of PEMFC Cathode Catalyst Layers. Issue 22 (27th September 2021) - Ott, Sebastian; Bauer, Andreas; Du, Fengmin; Dao, Tuan Anh; Klingenhof, Malte; Orfanidi, Alin; Strasser, Peter
Abstract: The analysis of the impact of the cathode catalyst layer pore structure on the membrane electrode assembly (MEA) cell performance of a PEMFC is presented. In this study, a pristine CMK‐3 catalyst carbon support material with well‐defined pore structure in the 3–6 nm range together with two nitrogen‐doped variants is analyzed against a commercial carbon black to achieve a better understanding of catalyst layer porosity‐performance relations. We used chemically N‐doped CMK‐3 catalyst to learn more about the effect of N‐doped porous catalyst supports on the concomitant transport properties and PEMFC cell performance. Chemical treatment using cyanamide was conducted to introduce a variety of N‐functionalities. A detailed in‐situ electrochemical investigation was combined with N2 ‐physisorption analysis. Based on their structural properties, the mesopore fractions and pore openings display a major role for reducing oxygen transport resistance and enhance Pt accessibility. We find that hierarchically ordered mesoporosity is superior to disordered porosity with prevalent micropore character: Analysis including adsorption electrochemical active surface area (ECSA), Pt‐accessibility, ionomer coverage, pore geometry, proton resistivity and transport loss we conclude the importance of a well‐defined mesoporous structure for its cell performance. Abstract : Oxygen reduction reaction : In this work, we studied the influence of the mesopore structure of the carbon support material towards MEA cell performance under dry and wet operating conditions. ECSA and oxygen mass transport within the catalyst layer are directly linked to the accessibility and pore openings of the supporting material.